Procalcitonin as a Predictive Marker of Incident Liver Disease - Finnberg‐Kim, Amanda; Pihlsgård, Mats; Önnerhag, Kristina; Melander, Olle; Enhörning, Sofia (Liver international, 2025)
ABSTRACT Background and Aims Previous studies have shown that procalcitonin (PCT) concentration is elevated in patients with liver disease without evidence of bacterial infection. We aimed to investigate the association between elevated PCT and the future risk of liver disease. Method PCT was measured in 3897 individuals without known liver disease in the Malmö Diet and Cancer Cardiovascular Cohort (MDC‐CC) and in 3854 individuals in the Malmö Preventive Project cohort (MPP). Cox proportional hazards regression models were used to analyse the risk of register‐verified incident liver disease by PCT levels. We performed our analyses in a pooled sample of both the MPP and MDC‐CC cohorts, as well as separate analyses for each cohort. Results 70 subjects in MDC‐CC and 49 subjects in MPP were diagnosed with non‐viral liver disease during a median follow‐up of 27.1 and 14.8 years, respectively. In multivariate adjusted models in the pooled sample, individuals with high PCT (> 0.05 ng/mL) had a significantly increased risk of developing liver disease compared to subjects with PCT concentrations below the cutoff (hazard ratio (HR) 3.4, 95% confidence interval (CI) 2.07–5.63, p < 0.001). The HR per standard deviation increase of log‐transformed PCT was 1.56 (95% CI 1.32–1.85, p < 0.001) in multivariate adjusted models. Separate cohort‐specific sensitivity analyses, including additional adjustment for C‐reactive protein, showed similar effect estimates as the pooled analyses. Conclusions Elevated concentration of PCT independently predicts non‐viral liver disease. These findings could have implications for risk assessment but also highlight the possibility of PCT as a direct cause of hepatocyte damage.